A mulher invisível: sentidos atribuídos à mulher e ao trabalho na gerência intermediária - Morgado, Ana Paula Dente Vitelli (2012)
This research aimed at exploring the meanings that women middle managers placed on themselves and on their work in this particular hierarchical position. In the Organizational Studies field, there is a vast literature that investigates sex segregation in organizations, looking for explanations why it continues to exist. There is also another set of bibliography that documents middle management particularities and how work is experienced by those in this position. However, there are few studies which focus on women as middle managers. The research was based on the social constructionist approach that is concerned with explaining the processes by which people come to describe and explain the world in which they live, including themselves. According to these ideas, reality is a process of social construction that is historically and culturally located; therefore, this research has considered relevant three historical contexts: contemporary society and its matters of social saturation as well as multiple and fragile identities; a brief history of women in society and work since the beginning of industrialization and mainly after the second half of the twenty century; and finally, the feminist movement issues which accounted for deep transformations in social arrangements after the 1970´s. The data was collected by interviewing 42 women middle managers who worked at national and multinational organizations based in São Paulo. The results revealed that women middle managers face a symbolic disappearance. They disappear from the private sphere of home when they wish to stay away from this place that means inequality although gave them a sense of identity in the past. They also disappear from the organization as a public sphere since it is a place where masculinities predominate and, paradoxically, are reinforced by women themselves. Adding to that, their daily lives are characterized by saturation, both at work and in personal life, dictated by the fast pace of work. In this context, this woman is everywhere, but at the same time seems to be nowhere. Although she is a manager, a mother, a wife, and she is responsible for the house, this research showed that she is not fully present in any of these places: in addition to her disappearance from home and from the public sphere of the organization, as a wife, she is not with her husband, as a mother, she is not with her kids and as a being has no time for herself. Thus, in view of this multiplicity of selves, the fragility of identity seems to be the outstanding feature of this woman´s life. As a way of dealing with these issues, this woman middle manager sets boundaries to her professional career, avoiding promotions to higher hierarchies and even setting plans for alternative careers as ways of managing her time constrains. These findings offer another view to understand the glass ceiling phenomenon in organizations.